PENGEMBANGAN LKPD MATEMATIKA BERBASIS ETNOMATEMATIKA PADA MOTIF BATIK JAMBI UNTUK KELAS III SD - Anggreyani, Risma; Sastrawati, Eka; Budiono, Hendra (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research aims to develop ethnomathematics-based Student Worksheets (LKPD) with Jambi batik motifs for Grade III Elementary School, as well as to evaluate its suitability. The method employed is Research and Development (RD) using the ADDIE model. Data was collected through validation questionnaires by validators, practitioners, and student responses at SD Negeri 182/I Hutan Lindung. The results showed that the LKPD was highly valid and practical, with high validation scores from content experts (4.9), media experts (5), and language experts (5), as well as positive responses from teachers and students. The conclusion drawn from this study is that ethnomathematics-based LKPD with Jambi batik motifs is highly suitable for mathematics learning in Grade III elementary schools.